Disorientasi Pengembangan Intelektual PTAIN, Pergeseran Wacana Studi Keislaman dalam Menghadapi Persaingan Pasar Kerja - Saleh, Fauzan (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The article analyzes the trends and impact of intellectual orientation shift occurring at PTAI recently. The development of Islamic knowledge at PTAI has been facing harder challenge. More intellectual scholars are not really keen on deepening their Islamic knowledge at tertiary education. This is contrary to the religious enthusiasm found in the society recently. There are two religious viewpoint shifts in our society. People are to be more religious by involving in Islamic teachings and halaqah, and, on the other hand, they do not want to be left behind in gaining earthly advantages. Deeping religious knowledge seriously does not attract them; therefore, Islamic study is not improving. Religion is seen as a practical need that can be studied instantly. As a result, people tend to focus on studies that are promising concrete earthly work.Â It seems that PTAI has been able to see this social trend shift so as to maintain its existence. As a consequence, orientation shift occurs and enlarged mandate takes place to accommodate them. In respond to it, institution change is a mustâ€”from Institute for Islamic Studies to Islamic University. In this instance, efforts have been done to legitimate the change. Eventually, the question to raise is how about the development mission of religious studies themselves then.